O ensino de LIBRAS: desafios e perspectivas docente em uma escola no município de Soure - VITELLI, Anderson Souza (2024)
This work is situated in the field of special education and discusses the challenges and perspectives of teaching LIBRAS in a school in the municipality of Soure/PA. The general objective of this study was to investigate the challenges and perspectives of teaching LIBRAS to deaf students in a regular classroom in a school in the municipality of Soure. The research is qualitative (Minayo, 2004). The data collection instrument was a semi-structured interview with the LIBRAS interpreter at the school. After data collection, content analysis was carried out according to Bardin (1977). The results show that the educational organization in the mu- nicipality of Soure, from the perspective of inclusive education, is recent and that the students of the degree course in Portuguese Language/LIBRAS themselves began to work to make the population of Soure aware of the rights to education of deaf people living in the city, many of whom had already passed the age of schooling. From this, it can be concluded that even though it is recognized by law as a legal means of communication and expression, especially for the deaf community, the Brazilian Sign Language (LIBRAS) is not yet a compulsory curricular component in schools, which makes the teaching of LIBRAS in educational institutions unpretentious and irrelevant.